“What do you think people feel?” Emotional climate during a pandemic: Adaptation and validation of a scale - Sousa,Cristina de (2021)
Abstract Our study examined the psychometric properties and factor structure of an instrument to assess emotional climate during the COVID-19 pandemic using a sample of 601 Portuguese individuals. Two sub-samples were created, one to perform an exploratory factor analysis (EFA), composed of 300 participants, and the other to conduct a confirmatory factor analysis (CFA), composed of 301 individuals. Two factors were found: positive and negative emotional climate. In the EFA, both factors established a negative and significant correlation. However, the CFA presented a better fit with two independent factors. Reliability analysis indicated acceptable values for both dimensions. There was also evidence of discriminant, convergent, and criterion validity. More negative emotions were perceived regarding the social climate. Results were discussed in the frame of different positive and negative psychosocial variables related to positive and negative emotional climates, as well as positive emotional climate as a resource for collective resilience.